Quality and safety assessment of chicken bilog sold in selected wet markets in Iloilo city. - Abian, Alyssa Anne Colonia
The Food and Agriculture Organization (FAO) of the United Nations estimates that by the last year 2030, developing countries will have an annual per capita consumption of around 37 kilograms of meat. The consumption of these products, however, entails risks such as the possibility that there were excess amounts of nitrites used, as well as the presence of pathogens which may cause food poisoning. One processed meat product available in the market is Chicken Bilog. The general objective of this study was to assess the quality of Chicken Bilog sold in selcted wet markets in Iloilo City. Chicken Bilog samples were subjected to microbiological analyses, physicochemical analyses and nitrite content determnination. The analyses were done in three runs. Results show that the mean Aerobic Plate Count (APC) of uncooked Chicken Bilog ranged from 6.7x107 CFU/g to 8.1 x 1010 CFU/g, while for the cooked samples, the mean APC ranged from 9.2 x 104 CFU/g to 1.7 x 106 CFU/g. For the Most Probable Number (MPN/g) of coliforms, both uncooked and cooked Chicken Bilog had >1100 MPN/g. The pathogens, namely, Escherichia coli, Salmonella and Staphylococcus aureus were also detected in both the uncooked and cooked Chicken Bilog. The water activity of both uncooked and cooked Chicken Bilog favored the growth of microorganisms having a water activity range of 0.952-0.961 for the uncooked Chicken Bilog, and 0.926-0.949 for the cooked samples. The pH values of Chicken Bilog also favored the growth of microorganisms with a pH range of 6.02-6.21 for the uncooked samples, and 5.96-6.21 for the cooked samples. Nitrite content analysis showed that the mean nitrite content of Chicken Bilog is 70.77 ppm, which is within the acceptable limit. Base on the guidelines for the assessment of microbiological quality of processed foods specifically for meat and meat products by the Food and Drug Administration (2013), the Aerobic Plate Count of the uncooked Chicken Bilog from all the selected wet markets exceeded the acceptable limits. As for the cooked samples, only the mean APC of the samples from location C was beyond the acceptable limits. In general, this study shows that Chicken is considered as unsafe for consumption, especially is heat treatment is not done properly.